2014
DOI: 10.1111/ecc.12184
|View full text |Cite
|
Sign up to set email alerts
|

Hope for a cure and altruism are the main motives behind participation in phase 3 clinical cancer trials

Abstract: It is necessary to carry out randomised clinical cancer trials (RCTs) in order to evaluate new, potentially useful treatments for future cancer patients. Participation in clinical trials plays an important role in determining whether a new treatment is the best therapy or not. Therefore, it is important to understand on what basis patients decide to participate in clinical trials and to investigate the implications of this understanding for optimising the information process related to study participation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 21 publications
(38 reference statements)
9
54
0
Order By: Relevance
“…One study 486 found that, even when participants recalled the involvement of chance, most also held other coexisting (and sometimes contradictory) views about how and why they had been allocated to the treatment or intervention and believed that they would receive the best treatment for them. Similarly, a number of studies have identified that personal benefits, hope, access to the most effective treatment, 492 and the enthusiasm and hopes of family and friends were often the driving force behind and key motivations for participation. 490 Such beliefs highlight the vulnerability of some groups and the risks that they are willing to take if there is a chance of survival, 493 and this may be an important factor for trials involving potentially disease course-modifying treatments.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…One study 486 found that, even when participants recalled the involvement of chance, most also held other coexisting (and sometimes contradictory) views about how and why they had been allocated to the treatment or intervention and believed that they would receive the best treatment for them. Similarly, a number of studies have identified that personal benefits, hope, access to the most effective treatment, 492 and the enthusiasm and hopes of family and friends were often the driving force behind and key motivations for participation. 490 Such beliefs highlight the vulnerability of some groups and the risks that they are willing to take if there is a chance of survival, 493 and this may be an important factor for trials involving potentially disease course-modifying treatments.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…At the same time, nonintentional harm may also affect individual people. For example, Godskesen et al (2015) report the motivating factors in which cancer patients volunteer for clinical trials include hope for health benefits in establishing better treatments and the willingness to help. Other survivors share their stories or engage in helping professions, such as the health services, following cancer survival in the UK (Cancer Recovery Foundation, 2007).…”
Section: Roots Of Altruismmentioning
confidence: 99%
“…For example, in qualitative research HIV-positive individuals, they "repeatedly voiced their desire to help others" (Reeves et al, 1999, p. 353). Those living with cancer also expressed altruistic motives for participating in clinical trials by helping to develop improved treatments for future patients (Godskesen et al, 2015;Truong et al, 2011). These findings suggest that personal ALTRUISM BORN OF SUFFERING IN NI 8 suffering may enhance helping acts.…”
mentioning
confidence: 95%
“…While altruism can be a significant motivator for participation, the notion that it is the only legitimate reason for participation in research is neither realistic nor desirable. Studies have demonstrated that altruism is not always the main factor driving participation in medical research and that subjects frequently have more than one reason for participation (McCann et al, 2010;Hunter et al, 2012;Godskesen et al, 2014). Relying only on altruism may be especially problematic for communities with a history of experiencing research abuses who may demand more tangible benefits from participation in genetic studies (Corbie-Smith et al, 1999).…”
Section: Discussionmentioning
confidence: 99%